1987
DOI: 10.1111/j.1476-5381.1987.tb11218.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated intravenous administration of haem arginate upon hepatic metabolism of foreign compounds in rats and dogs

Abstract: 1 Haem arginate is a new haem compound, recently introduced for the treatment of acute hepatic porphyrias. Porphyrias are characterized biochemically by decreased formation ofhaem due to defects in certain enzyme activities involved in the haem biosynthesis. 2 Haem is essential for cell respiration and oxidative biotransformation. Hepatic drug metabolism, haem biosynthesis and catabolism were investigated after repeated intravenous administration of haem arginate in connection with toxicity studies. 3 The dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In nonporphyric animals, haematin (4 mg kg-) impaired hepatic drug metabolism (Muller-Eberhard et al, 1983), but haem arginate during 1 month of daily intravenous doses equivalent to 3-4 mg haem kg-1 did not change the concentration of cytochrome P-450 or numerous other parameters of drug metabolism (Tokola, 1987). This difference may be due, for example, to the poor stability of haematin, causing decomposition products with toxic actions (Goetsch & Bissell, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In nonporphyric animals, haematin (4 mg kg-) impaired hepatic drug metabolism (Muller-Eberhard et al, 1983), but haem arginate during 1 month of daily intravenous doses equivalent to 3-4 mg haem kg-1 did not change the concentration of cytochrome P-450 or numerous other parameters of drug metabolism (Tokola, 1987). This difference may be due, for example, to the poor stability of haematin, causing decomposition products with toxic actions (Goetsch & Bissell, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The first involves CO [20] produced from the haem oxygenase reaction following induction of HO 1 by haem. Induction of HO 1 mRNA expression, protein levels and/or activity by haem arginate has been demonstrated in rats, dogs and humans [23][24][25][26][27]. The second mechanism involves PLP depletion following its consumption by kynurenine aminotransferase (KAT) and kynureninase (kynase) following activation of liver TDO by haem (see further below).…”
Section: Increased Haem Availabilitymentioning
confidence: 99%
“…A time-course study in rats [23] showed that HO 1 induction by haem arginate is highest (~ 5-fold) at 5-7h and remains pronounced (~3-fold) at 24h after the last of 4 daily injections of 15 mg/kg body weight each, with comparable levels of induction by hemin and haem arginate. At 24h, loss of haem is apparent from the decreased levels of cytochrome P-450 and impaired metabolism of arachidonic acid [23] and several drugs [24]. Induction of HO 1 protein and activity in humans was still pronounced at 48h after intravenous administration of haem-albumin [26].…”
Section: Increased Haem Availabilitymentioning
confidence: 99%
See 1 more Smart Citation